2014
DOI: 10.2310/8000.2013.131048
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status of emergency department users in Ontario, 2003 to 2009

Abstract: Objective: Emergency department (ED) overcrowding in Canada is an ongoing problem resulting in prolonged wait times, service declines, increased patient suffering, and adverse patient outcomes. We explored the relationship between socioeconomic status (SES) and ED use in Canada's universal health care system to improve our understanding of the nature of ED users to both improve health care to the most deprived populations and reduce ED patient input. Methods: This retrospective study took information from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…Education and income have been shown to correlate strongly with ED usage, regardless of the actual cost or availability of emergency services within the region. 15,17 These variables represent socioeconomic modifiers that future efforts to reduce rebound to the ED in patients treated with shunts will have to consider, and they have already been identified as relevant for other disease entities as well. 11,12 In certain institutions, patient literacy programs and early postoperative appointments have been implemented, with some success, to bridge the gap in education and social support suffered by these patients.…”
Section: At-risk Patient Groups Versus Preventabilitymentioning
confidence: 99%
“…Education and income have been shown to correlate strongly with ED usage, regardless of the actual cost or availability of emergency services within the region. 15,17 These variables represent socioeconomic modifiers that future efforts to reduce rebound to the ED in patients treated with shunts will have to consider, and they have already been identified as relevant for other disease entities as well. 11,12 In certain institutions, patient literacy programs and early postoperative appointments have been implemented, with some success, to bridge the gap in education and social support suffered by these patients.…”
Section: At-risk Patient Groups Versus Preventabilitymentioning
confidence: 99%
“…[9][10][11][12] Efforts to address high-cost use have primarily been limited to case management of high-risk patients, such as the elderly and those with multi-morbidity. 12,13 Few studies, however, have highlighted the importance of the upstream determinants of high-cost use. 7,10,[13][14][15][16][17] Despite universal insurance coverage in Canada's healthcare system, Dunlop et al 11 observed a distinct relationship between SES and frequent users of primary care in the 1994 National Population Health Survey.…”
Section: Introductionmentioning
confidence: 97%
“…12,13 Few studies, however, have highlighted the importance of the upstream determinants of high-cost use. 7,10,[13][14][15][16][17] Despite universal insurance coverage in Canada's healthcare system, Dunlop et al 11 observed a distinct relationship between SES and frequent users of primary care in the 1994 National Population Health Survey. It is reasonable to expect that the SES-health gradient fundamental to so many inequities in health outcomes would extend to HCUs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study suggested that the impact of macroeconomic policies on the health of people in the country must be constantly measured and before the implementation of new policies, positive or negative impacts of them must be investigated. Our results based on the experts' opinions showed that weak financial protection plans and inadequate coverage of insurances, a high level of out of pocket in health financing have negative impact on community health (55)(56)(57)(58). Macroeconomic policies such as the subsidies have great impact on the community health in the country and the effects should be measured.…”
Section: Discussionmentioning
confidence: 99%